Using FLOSS in distance education - Banek Zorica, Mihaela (2005)
The workshop "Using FLOSS in distance education" (FLOSS being Free/Libre and Open Source Software) would cover a topic of using different FLOSS software solutions in distance education based on author's experience in the field. Both authors were involved in the planning, selection and implementation process of distance education system on the Faculty of philosophy, University of Zagreb.